2007
DOI: 10.1177/0363546507299531
|View full text |Cite
|
Sign up to set email alerts
|

Avulsion Fracture of the Lateral Ankle Ligament Complex in Severe Inversion Injury

Abstract: Avulsion fracture of the lateral ankle ligaments in cases of severe inversion injury is more common than previously believed. Because of the high incidence and difficulty of detection in children, a high level of suspicion is necessary in order to obtain an accurate diagnosis of avulsion fracture in cases of severe inversion injury and to achieve adequate stability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
58
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 21 publications
2
58
0
1
Order By: Relevance
“…(iii) The establishment of the anterior channel of the lateral malleolus under arthroscopy should be carried out in the safe area to avoid injury to the superficial peroneal nerve and sural nerve. (iv) The small bone mass of lateral malleolus avulsion can be removed to prevent the formation of corpus liberum and impact. (v) During the operation, the position of the anchor should be located at the middle point of the footprint region of the distal fibula, and the bone freshening of the footprint region should be carried out before inserting the anchor to facilitate better healing of ATFL.…”
Section: Discussionmentioning
confidence: 99%
“…(iii) The establishment of the anterior channel of the lateral malleolus under arthroscopy should be carried out in the safe area to avoid injury to the superficial peroneal nerve and sural nerve. (iv) The small bone mass of lateral malleolus avulsion can be removed to prevent the formation of corpus liberum and impact. (v) During the operation, the position of the anchor should be located at the middle point of the footprint region of the distal fibula, and the bone freshening of the footprint region should be carried out before inserting the anchor to facilitate better healing of ATFL.…”
Section: Discussionmentioning
confidence: 99%
“…Many of these lateral ligament sprains involve additional injuries to other soft tissue structures (Fallet et al, 1998). In severe sprains, avulsion fractures of the lateral malleolus are common in children and in adults over 40 years old (Haraguchi et al,2007).…”
Section: Epidemiology and Fracture Classificationmentioning
confidence: 99%
“…Like many other parts of the body, the ankle is fractured more often in young men and older women (Yde,1980; Daly et al,1987; Jensen et al,1998). Comminuted fractures, multiple fractures, and avulsion fractures occur more often in older patients and as the result of low‐energy trauma (Bauer et al,1987; Court‐Brown and Caesar,2006; Haraguchi et al,2007; Aktas et al,2008). On the basis of the age and sex distribution of injured patients, Court‐Brown and Caesar (2006) concluded that bimalleolar and trimalleolar fractures of the ankle should be regarded as predominantly osteoporotic.…”
Section: Epidemiology and Fracture Classificationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, an isolated injury to the CFL ligament has rarely been reported (3). Theoretically, the latter injury pattern should involve an inversion type of mechanism with the ankle in extreme dorsiflexion to entirely avoid a concomitant injury to the ATFL (2).…”
Section: Discussionmentioning
confidence: 99%